Identification of Genetic Loci for Grain Traits and Disease Resistance Reveals a Potential Trade-Off in Rice - Yulin Jia; Melissa H. Jia; Heather Box (PhytoFrontiers)
Understanding how plants utilize limited resources for reproductivity and disease resistance can improve the efficiency of plant breeding. In the present study, we mapped genes for grain traits, including grain length and width and thousand grain weight (TGW). A previously constructed linkage map of a recombinant inbred line population (MHM) was used, which was derived from a cross between an indica restorer rice variety (Minghui 63) and a temperate japonica rice variety (M-202). The MHM population was grown in replicated field plots, and grain trait data were collected. Upon a 3-year field evaluation, a total of 16 loci were mapped on 9 of 12 chromosomes, including 7 for grain length, 4 for grain weight, and 5 for TGW. A TGW locus (qTGW2) and a grain width locus (qWIG2.2) were mapped at the known blast resistance locus qBLAST2 on chromosome 2 that harbors a major blast resistance allele Pi-b. Another TGW locus (qTGW3.3) and a grain length locus (qLNG3.3) were mapped at qBLAST3 on chromosome 3. These results reveal potential trade-offs between disease resistance and productivity, which are important for breeders to develop high-yielding and disease-resistant rice varieties. [Figure: see text] The author(s) have dedicated the work to the public domain under the Creative Commons CC0 “No Rights Reserved” license by waiving all of his or her rights to the work worldwide under copyright law, including all related and neighboring rights, to the extent allowed by law, 2024.